Experience and sexuality education in creation of audiovisual installation (Research, Society and Development, 2021)
Experience and education on sexuality is a unity of things / events experienced by individuals / groups regarding sex and sexuality which are then reduced to an informal educational structure. The purpose of this research is to explain  the concept of artwork that underlies the creation of the audiovisual installation and the process of visualization of artwork on the creation of audiovisual installation. The media for creating works that are applied is an audiovisual installation art. Inspired by the previous works of Julian Rosefeldt (Manifesto), Gerda Wegener (Solitaire), Mella Jaarsma (Potong Waktu) and Halsey (Album Manic). The method of creation is based on Laura H. Chapman's theory with three stages, namely Inception of Idea, Elaboration and Refinement, and Execution in a Medium.